2018
DOI: 10.1152/ajplung.00208.2018
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages from the upper and lower human respiratory tract are metabolically distinct

Abstract: The function and cell surface phenotype of lung macrophages vary within the respiratory tract. Whether the bioenergetic profile of macrophages also differs depending on location within the lung is currently unknown. This study sought to characterize the bioenergetic profile of macrophages sampled from different locations within the respiratory tract at baseline and in response to ex vivo xenobiotic challenge. Surface macrophages recovered from healthy volunteers by induced sputum and by bronchial and bronchoal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…The differences in ΔΨm and resistance to mitochondrial dysfunction that was observed in this study might also be of evolutionary significance and has to be explored further. While we acknowledge the limitation of this study that might arise from the use of hMDMs (which is the most widely used model of human macrophages) in comparison to BMDMs from mouse, our findings are in accordance with a previous observation that human lung macrophages displayed no metabolic alterations upon LPS stimulation in vitro [21]. The increased glycolysis characteristic of mouse macrophages with mitochondrial dysfunction appears to play a role in cell survival as previously shown for astrocytes [22].…”
Section: Resultssupporting
confidence: 91%
“…The differences in ΔΨm and resistance to mitochondrial dysfunction that was observed in this study might also be of evolutionary significance and has to be explored further. While we acknowledge the limitation of this study that might arise from the use of hMDMs (which is the most widely used model of human macrophages) in comparison to BMDMs from mouse, our findings are in accordance with a previous observation that human lung macrophages displayed no metabolic alterations upon LPS stimulation in vitro [21]. The increased glycolysis characteristic of mouse macrophages with mitochondrial dysfunction appears to play a role in cell survival as previously shown for astrocytes [22].…”
Section: Resultssupporting
confidence: 91%
“…8 However, bioenergetic characterization of the innate immune system has been limited primarily to macrophages, while neutrophils have been largely ignored. 9,10 Furthermore, the ability of toxicants to alter neutrophil bioenergetics and downstream functions remains unclear. Our lab has demonstrated that the flavoring chemical cinnamaldehyde significantly affects cellular bioenergetics, which in turn causes impairment of key innate immune functions of respiratory epithelial cells.…”
mentioning
confidence: 99%
“…They may increase the respiratory rate or glycolysis to meet the requirements. We therefore assessed mitochondrial respiration, ATP generation, and the balancing of oxygen consumption (OCR, Figure 3 A,B,D) and extracellular acidification rate (ECAR, Figure 3 C,D), key indicators of mitochondrial respiration and glycolysis, respectively [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 39 ]. Indeed, absolute basal OCR in the presence of full nutrients and supplements (pyruvate, glutamine and glucose) was much higher in shNXN cultures ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial respiration and extracellular acidification were analyzed simultaneously on a Seahorse XFp instrument using an XFp “Cell Mito Stress Test” (Agilent Technologies, 76337 Waldbronn, Germany) [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. This is a plate-based live cell assay for monitoring of oxygen consumption and extracellular acidification rates in live cells.…”
Section: Methodsmentioning
confidence: 99%